I know who I am in green food consumption - Ling, Wang; Chong, Kim Mee; Lo, May Chiun; Cham, Tat Huei; Tan, Tze Horng (Asia Business Research Corporation Limited, 2024)
The study investigates the factors influencing young Chinese consumers’ intention to consume green food. This study combined the Theory of Planned Behaviour and the Normative activation model theory to determine whether green self-identify (GSI), awareness of environmental consequences (AEC), and subjective norms (SN) are related to green food consumption intention (GFI) through the mediating effects of green attitude (GA) and personal norms (PN). The study was conducted in the world’s largest developing country, China. Quantitative methods were used in this study. Data were collected using a customised and validated survey instrument from 318 young consumers aged 14-35 in China. The data analysis revealed that GSI, SN, and AEC were significant predictors of PN and GA. It implies that PN and GA directly influenced young consumers’ GFI and that trust moderated the relationship between PN, GA, and GFI. The findings will significantly assist government officials, green marketers, and practitioners in recognising the role of GFI and trust in the evolution of young Chinese consumers’ attitudes towards green food and their intention to consume green food, thus contributing to developing promotional policies and marketing strategies.